Why architecture matters - Goldberger, Paul (New Haven : Yale University Press, 2022)
A classic work on the joy of experiencing architecture, with a new afterword reflecting on architecture's place in the contemporary moment (3z(BArchitecture begins to matter,(3y (Bwrites Paul Goldberger, (3z(Bwhen it brings delight and sadness and perplexity and awe along with a roof over our heads.(3y (BIn Why Architecture Matters, he shows us how that works in examples ranging from a small Cape Cod cottage to the vast, flowing Prairie houses of Frank Lloyd Wright, from the Lincoln Memorial to the Guggenheim Bilbao. He eloquently describes the Church of Sant'Ivo in Rome as a work that (3z(Bembraces the deepest complexities of human imagination.(3y (BIn his afterword to this new edition, Goldberger addresses the current climate in architectural history and takes a more nuanced look at projects such as Thomas Jefferson's academical village at the University of Virginia and figures including Philip Johnson, whose controversial status has been the topic of much recent discourse. He argues that the emotional impact of great architecture remains vital, even as he welcomes the shift in the field to an increased emphasis on social justice and sustainability.s
Title -- Copyright -- Dedication -- Contents -- Introduction -- One Meaning, Culture, and Symbol -- Two Challenge and Comfort -- Three Architecture as Object -- Four Architecture as Space -- Five Architecture and Memory -- Six Buildings and Time -- Seven Buildings and the Making of Place -- Afterword: Architecture, Power, and Pleasure -- Glossary -- A Note on Bibliography -- Acknowledgments -- Illustration Credits.
Unlimited user
Includes index.
Keywords: ARCHITECTURE AND SOCIETY; ARCHITECTURE -- AESTHETICS